Impacts on and damage to European forests from the 2018–2022 heat and drought events - F. Knutzen; P. Averbeck; C. Barrasso; C. Barrasso; L. M. Bouwer; L. M. Bouwer; B. Gardiner; J. M. Grünzweig; S. Hänel; K. Haustein; K. Haustein; M. R. Johannessen; et al. (Natural Hazards and Earth System Sciences)
Drought and heat events in Europe are becoming increasingly frequent due to human-induced climate change, impacting both human well-being and ecosystem functioning. The intensity and effects of these events vary across the continent, making it crucial for decision-makers to understand spatial variability in drought impacts. Data on drought-related damage are currently dispersed across scientific publications, government reports, and media outlets. This study consolidates data on drought and heat damage in European forests from 2018 to 2022, using Europe-wide datasets including those related to crown defoliation, insect damage, burnt forest areas, and tree cover loss. The data, covering 16 European countries, were analysed across four regions, northern, central, Alpine, and southern, and compared with a reference period from 2010 to 2014.